Modified Frailty Index Predicts Postoperative Complications following Panniculectomy in the Elderly - Jasmine Lee, BA; Allyson R. Alfonso, BS, BA; Rami S. Kantar, MD, MPH; Gustave K. Diep, MD; Zoe P. Berman, MD; Elie P. Ramly, MD; David A. Daar, MD, MBA; Jamie P. Levine, MD; Daniel J. Ceradini, MD (Plastic and Reconstructive Surgery, Global Open, 2020)
Background:. Due to the high complication rate of panniculectomies, preoperative risk stratification is imperative. This study aimed to assess the predictive value of the 5-item modified frailty index (mFI-5) for postoperative complications in the elderly following panniculectomy. Methods:. A retrospective cohort study of the American College of Surgeons National Surgical Quality Improvement Program database for patients over the age of 65 years who underwent a panniculectomy between 2010 and 2015 was conducted. The mFI-5 score was calculated for each patient based on the presence of diabetes, hypertension, congestive heart failure, chronic obstructive pulmonary disease, and dependent functional status, and an mFI-5 score of 2 was used as a cutoff. Multivariate logistic and linear regression analysis was used to determine the validity of the mFI-5 as a predictor of postoperative complications. Results:. A total of 575 patients were analyzed. Patients with an mFI-5 score of 2 or more (421; 73.2%) had significantly higher rates of wound complications (19.5% versus 12.8%; P = 0.03), overall complications (33.8% versus 19.5%; P < 0.001), and significantly longer hospital length of stay (3.6±5.0 versus 1.9±3.0; P < 0.001). mFI-5 score of 2 or more was an independent risk factor for wound complications (odds ratio, 1.26; 95% confidence interval, 1.08–2.20; P = 0.04) and overall complications (odds ratio, 1.34; 95% confidence interval, 1.09–2.15; P = 0.02). Conclusions:. Frailty, as measured by the mFI-5, holds a predictive value regarding outcomes of wound complications and overall complications in elderly patients after panniculectomy. The mFI-5 score can be used to identify high-risk patients before surgery.